Aktualisasi Landasan Yuridis Organisasi Keagamaan Dalam Pembangunan (Kajian Konteks Kekristenan) - Hasudungan Simatupang (Institut Agama kristen Negeri Tarutung, 2022)
Abstract: Formally, the juridical basis provides an order to regulate all religious organizations in Indonesia, including Christian religious organizations that both show obedience both independently and in groups in carrying out organizations and activities as evidence of being active in defending the right to life. Obedience to Christian religious organizations is associated with activities including actualizing the application of legal arguments (juridical actualization) to the success of national development as a form of practicing Christianity into an exciting obligation in line with the vision and mission based on the agreement of the organization's organs without contradicting the laws and regulations. The juridical actualization of Christian religious organizations throughout development is focused on: preaching the gospel, religious harmony as social capital for development, participation of Christian religious social groups, utilizing religious pulpits, providing advice and input, interpreting religious teachings for the success of development, forming religious attitudes, establishing schools, horizontal, functional cooperation, partnership in harmony, actively participating in activities at the meeting forum. Keywords: Actualization, Juridical, Religious Organizations Abstrak: Secara formal landasan yuridis memberikan tatanan mengatur seluruh organisasi keagamaan di Indonesia, termasuk di dalamnya organisasi keagamaan Kristen sama-sama menunjukkan kepatuhan baik secara mandiri, maupun kelompok dalam menjalankan organisasi dan aktivitas sebagai bukti aktif diri mempertahankan hak hidup. Ketaatan organisasi keagamaan Kristen dikaitkan dengan aktivitas meliputi aktualisasi penerapan dalil-dalil hukum (aktualisasi yuridis) menyukseskan pembangunan nasional sebagai wujud pengamalan agama Kristen menjadi kewajiban yang menggairahkan sejalan dengan visi misi berdasarkan kesepakatan organ organisasi tanpa bertentangan dengan peraturan perundang-undangan. Aktualisasi yuridis organisasi keagamaan Kristen seantero pembangunan difokuskan pada: Pekabaran Injil, kerukunan umat beragama sebagai modal sosial pembangunan, peran serta kelompok-kelompok sosial keagamaan Kristen, memanfaatkan mimbar agama, memberikan saran dan masukan, memaknai ajaran agama menyukseskan pembangunan, membentuk sikap religious, pendirian sekolah-sekolah, kerja sama horizontal, fungsional, kemitraan dalam kerukunan, aktif mengikuti kegiatan pada wadah pertemuan. Kata Kunci: Aktualisasi, Yuridis, Organisasi Keagamaan